'Un rire nouveau': Action Française and the art of political satire - Wardhaugh, J (Oxford University Press, 2008)
Action Française was one of the most notorious political movements of the Third Republic, and its intellectual influence is widely recognized. Yet the theatre of Action Française remains almost unknown. Based on hitherto neglected archives, this article reveals the close relationship between the plays and revues of Action Française and its literary and political ambitions. First, it examines Maurice Pujo's theory of counter-revolutionary theatre and his intention to provoke a 'new laugh' at the Republic through the development of political satire on the classical model. Secondly, it analyses the 1907 production of Pujo's Les Nuées (modelled on Aristophanes' The Clouds) and the subsequent development of musical revues by the Camelots du Roi. Finally, it discusses the significance of this political theatre and suggests its potential to shed light on a social and cultural life that has hiterto remained behind the scenes.